Replication Data for: Estimates of the size distribution of meteoric smoke particles from rocket-borne impact probes - Antonsen, Tarjei; Havnes, Ove; Mann, Ingrid (DataverseNO, 2017)
Contains raw PCM data streams for the MAXIDUSTY rocket launches, as well as specific files for the MUDD and DUSTY instruments used to produce the resuts in the paper "Estimates of the size distribution of meteoric smoke particles from rocket-borne impact probes". Naming and formatting of MATLAB-files (.mat): For MXD-1, MUDD files are separated into .mat files in the format: "M3G1_straightened" - Where 'M3' denotes "MUDD 3" and 'G1' denotes 'Grid 1'. Grid 2 is denoted by G2, and Bottom plate is denoted by BP. BP currents have additional information about the retarding potential, e.g. "M2BP_m2" (MUDD 2, Bottom plate, -2V). Altitudes files are formatted e.g. "Alt_13_8" which denotes Altitude, Flight 1 (MXD-1), MUDD 3, Retarding potential 8V. For MXD-1B, The file name formatting is the same, however a 'B' is added in the file name, e.g.: "Alt_1B3_8" or "M2BBP_m2". The files can be directly loaded into Matlab with the load('')-function. Formatting for tab-separated text files (.txt): There is one file for each respective retarding potential for each respective MUDD-probe. The altitude is given in the same file, i.e. the left column gives payload altitude in meters, and the right column gives MUDD bottom plate potential in nano-Amperes. The naming convention is the same as for the.mat files, such that 'M1BBP_m2.txt' contains the data for MUDD-1 on MXD-1B, for retarding potential -2V ("m2"). NB: Note that this is retarding for negative particles, so that a negative potential becomes attractive. For PCM-decoding of the raw telemetry signal, either Andøya Space Center or the responsible author can be contacted for decoding software and telemetry setup format. The .bin-files contains the complete flight-data for both MAXIDUSTY-flights.